Student Creativity Through the Use of Chromebooks in Biology Learning at SMAS IT Darul Istiqamah - AH, Fakhirah; Hikmah Rusdi; Pertiwi Indah Lestari (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research aims to analyze and describe student creativity through the use of Chromebooks in Biology learning at SMAS IT Darul Istiqamah. As an educational institution proactive in technological innovation and holding Google Reference School status, SMAS IT Darul Istiqamah has extensively integrated Chromebooks into its teaching and learning process. This descriptive qualitative research employed interviews with 15 students from Grades X, XI, and XII, as well as the Biology Teacher and the Head of School. The findings indicate that Chromebooks significantly facilitate student creativity in Biology learning through various digital manifestations. Students are able to produce innovative works such as 3D cell models, collaborative digital comics, and Artificial Intelligence (AI)-based applications like Teachable Machine, reflecting their unique visualization and application of Biology concepts. The devices also support collaborative creative processes and are effective in enhancing student focus by reducing distractions. Furthermore, Chromebooks facilitate the exploration of creative ideas through differentiated learning and the utilization of AI, while simultaneously increasing student motivation and engagement to become producers of innovative works. These findings are reinforced by the perspectives of the teacher and head of school, who observe the positive impact of Chromebooks on creativity and a conducive learning environment.